Anthropogenic and environmental factors determine occupancy and rarity of large carnivores in the Omo Valley, southwest Ethiopia - Tsyon Asfaw; Claudio Sillero‐Zubiri; Herwig Leirs; Fikirte Gebresenbet; Hans Bauer (Ecological Solutions and Evidence, 2025)
Abstract Large carnivores in Ethiopia are declining in numbers and range due to human population pressure, habitat fragmentation and loss, compounded by low political interest for conservation. To conserve large carnivores, it is important to study the impact of these factors on their occupancy. For this purpose, un‐baited camera traps were deployed in Chebera Churchura, Maze and Omo National Parks and Tama Community Conservation Area using a 25 km2 grid for 2‐month periods in each Protected Area from 2020 to 2022. We tested the effects of environmental and anthropogenic covariates on carnivore occupancy while accounting for imperfect detection using a multispecies occupancy model. We recorded all six large carnivores from Omo Valley. However, the number of large carnivores and their level of detection vary across the study sites; Omo National Park is the only Protected Area where all species were recorded. Maze National Park had the highest number of lion detections and the lowest number of leopard and spotted hyaena detections, but its small size led to inconclusive results from any further analysis. Due to low densities, detections were insufficient to analyse the occupancy of lion, cheetah, striped hyaena and African wild dog in Omo and Chebera Churchura National Parks and the occupancy of any large carnivores in Maze and Tama. The mean marginal occupancy probability of the leopard was highest in Chebera Churchura and lowest in Omo, and this was the reverse for the spotted hyaena. The occupancy of the spotted hyaena and leopard was determined by prey in Omo and by elevation in Chebera Churchura National Parks. Furthermore, both species visit areas with human settlement in Omo and Chebera Churchura National Parks. Practical implication: We explore strategies to improve large carnivore conservation in the area. We highlight the limitations of camera trapping and the importance of conserving large carnivores in the larger landscape of Omo Valley.